The Effectiveness of The Directorate of Community Development in Preventing Offences and Crimes in the Jurisdiction of the Bali Police Force - Putra, I Made Bagus Aldi Marantika; Wulandari, Ni Gusti Agung Ayu Mas Tri (Dinasti Research, 2025)
Ditbinmas Polda Bali as a field of implementing preventive police duties or preventing the occurrence of a crime by conducting activities such as coordination, supervision and guidance in the community. This paper aims to find out, analyse and examine the effectiveness of Ditbinmas Polda Bali in carrying out its duties to prevent violations and crimes in the jurisdiction of Polda Bali. The effectiveness of Ditbinmas Polda Bali in carrying out its duties to prevent violations and crimes in the jurisdiction of Polda Bali is that it has been running effectively, this is based on several indicators in the theory of legal effectiveness for example, aspects pertaining to the police, the infrastructure, the community, and the culture that have been carried out properly by Ditbinmas Polda Bali, namely through the implementation of guidance to the community through coordination, supervision and guidance activities on forms of self-initiated security, special police and cooperation activities in maintaining community security and order so as to prevent crimes and violations, especially in the jurisdiction of Polda Bali.